Contribution of postsynaptic T‐type calcium channels to parallel fibre‐Purkinje cell synaptic responses - Ly, Romain (J Physiol, 2016)
At the parallel fibre‐Purkinje cell glutamatergic synapse, little or no Ca(2+) entry takes place through postsynaptic neurotransmitter receptors, although postsynaptic calcium increases are clearly involved in the synaptic plasticity. Postsynaptic voltage‐gated Ca(2+) channels therefore constitute the sole rapid postsynaptic Ca(2+) signalling mechanism, making it essential to understand how they contribute to the synaptic signalling. Using a selective T‐type calcium channel antagonist, we describe a T‐type component of the EPSC that is activated by the AMPA receptor‐mediated depolarization of the spine and thus will contribute to the local calcium dynamics. This component can amount up to 20% of the EPSC, and this fraction is maintained even at the high frequencies sometimes encountered in sensory processing. Modelling based on our biophysical characterization of T‐type calcium channels in Purkinje cells suggests that the brief spine EPSCs cause the activated T‐type channels to deactivate rather than inactivate, enabling repetitive activation.